TLC phytochemical screening in some Nigerian loranthaceae (2010)
The phytochemical screening of specimens of the family Loranthaceae collected from the field was carried out with a view to ascertaining chemical constituents present and determining their importance in the taxonomic delimitation of the taxa. Thirty field collections from various localities were screened for secondary metabolites such as alkaloids, anthraquinones, terpenoids and ketones using thin layer chromatography (TLC). Most of the samples tested slightly positive for alkaloids, anthraquinone-related compounds, terpenoids and terpenoidrelated compounds but ketonic compounds were of rare occurrence in all the samples. The chemical profile was useful in separating the collections of Phragmanthera from the other two genera while the collections of Globimetula were found embedded in Tapinanthus. The secondary metabolites obtained however showed the relative affinity of the Nigerian species of Tapinanthus. It is concluded that chemical characters may only be used as supporting evidence in the identification and delimitation of the taxa.